Cation effect on electronic, optical and thermoelectric properties of perovskite oxynitrides: Density functional theory. (1st March 2020) - Mahmood, Amjid; Azam, Sikander; Irfan, Muhammad; Kamran, Muhammad Arshad; Alharbi, Thamer; Majid, Abdul; Iqbal, Muhammad Waqas; Muhammad, Shabbir; Al-Sehemi, Abdullah G.; Khan, Saleem Ayaz; Goumri-Said, Souraya
Abstract: Perovskite oxynitride are of great interest due to their use as photo-catalysts. We investigated the electronic, thermoelectric and optical properties of ATaO2 N (A = Ba, Sr, Ra) with generalized gradient plus Hubbard approximation (GGA + U). In electronic properties, we have computed, for each compound, densities of states (total and partial), band structure to extract their band gaps, nature and transition probability when the cation changes. Optical properties were explored by calculating dielectric constant ε (ω), refractive index n (ω), reflectivity R (ω), optical loss L (ω), and absorption coefficient I (ω) response against different photon energies. In order to examine the possibility of using these compounds in thermoelectric devices, we calculated their transport properties from Boltzman transport theory. We examined their thermal conductivity κ, electrical conductivity σ, seebeck coefficient S, power factor PF and dimensionless figure of merit ZT.